Understanding the associations between personality traits and mental health in people with epilepsy and healthy controls - Kang, Weixi (Frontiers in Psychology, 2023)
Objectives The aim of the current study was to test how epilepsy could moderate the associations between Big Five personality traits and mental health. Methods This cross-sectional study analyzed data from Understanding Society: UK Household Longitudinal (UKHLS), which relies on a complex multi-stage stratified sampling design. Personality traits were measured by the Big Five inventory whereas mental health where measured by the GHQ-12. A hierarchical regression and two multiple regressions were performed on 334 people with epilepsy with a mean age of 45.14 ± 15.88 years old (41.32% males) and 26,484 healthy controls (42.5% males) with a mean age of 48.71 ± 17.04 years old. Results Neuroticism was positively related to worse mental health in both people with epilepsy and healthy controls with a stronger relationship in people with epilepsy, but Conscientiousness was negatively related to worse mental health in both people with epilepsy and healthy controls. Moreover, Openness and Extraversion were negatively related to worse mental health in healthy controls but not in people with epilepsy. Conclusion Personality traits are closely related to mental health in both people with epilepsy and healthy controls. Clinicians should use findings from this study to detect people with epilepsy who may be at high risk of poor mental health based on their personality traits.